Adsorption Study of Rhodamine –B Dye on Plant (Citrus Leaves) - Ahlam M. Farhan; Ahlam M. Zaghair; Hussein I. Abdullah (Baghdad Science Journal, 2022)
The current research includes the adsorption of Rhodmine-B Dye on the surface of Citrus Leaves using the technique of UV. Vis spectrophotometer to determine data of quantitative adsorption at various contact time, ionic strength, PH and temperature conditions. As a function of temperatures 25,35,45,55 0C, the dsorption phenomenon was examined, and the results showed that Rhodamine-B adsorption Citrus leaves rose with increasing temperatures on the surface (endothermic process). Using various NaCl solution concentrations, the effect of ionic strength on adsorption has also been studied. Increasing the importance of ionic strength has been shown to improve the amount of adsorption of Rhodamine-B on citrus leaves at constant temperatures.The quantity of Rh-B dye that was adsorbed on the citrus leaves was increased with increasing the PH of the solution in rang 3-7. Then the results were subjected to the practical results obtained with the use isotherms of the Langmuir, Frendelsh, and Temkin. The results can be shown that the isotherm suitable for adsorption applies to Ferndelsh and Temkin. The thermodynamic functions (the amount of change in enthalpy, the amount of change in entropy and the amount of change in the free energy of Gibbs) were also studied, and it was found that the thermodynamic results of the adsorption process of the Rhodamine-B dye on the powder of citrus leaves are endothermic and an automatic adsorption process.